Research on the typical microstructures and contact angles of hydrophobic plant leaves. (1st April 2020) - Yi, Meirong; Wu, Liting; Liu, Luqi; Zhang, Pengxiang; Li, Xiaobing
Abstract : As well known, plant leaves exhibit a striking diversity of surface structures through billions of years of evolution. However, there are many issues remain unknown in the surface wettability of plant leaves. In this work, four kinds of typical plant leaves found in Nanchang University were introduced, by means of wettability and surface micromorphology with the aid of contact angle measurement and scanning electron microscopy. The surface structural models of these leaves with respect to their surface morphologies were established in terms of bionics. Meanwhile, the apparent contact angles on given surfaces were calculated using the Cassie–Baxter model. In addition, the effects of geometrical parameters of leaf surfaces on the contact angle were investigated using the Matlab software.